The Kantian Philosophy of Space - Garnett, Christopher Browne (Columbia University Press, 1939)
Presents an examination of Kant's views of space as he developed them between 1747 and 1787. Considers his views in relation to the theories on space from Newton and Leibniz and also his contemporaries, S. Alexander, Whitehead, and C. D. Broad